2015
DOI: 10.1186/s13018-015-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cartilage composite utilizing porous tantalum, fibrin, and rabbit chondrocytes for treatment of cartilage defect

Abstract: ObjectiveFunctional tissue engineering has emerged as a potential means for treatment of cartilage defect. Development of a stable cartilage composite is considered to be a good option. The aim of the study was to observe whether the incorporation of cultured chondrocytes on porous tantalum utilizing fibrin as a cell carrier would promote cartilage tissue formation.MethodsRabbit articular chondrocytes were cultured and seeded onto tantalum with fibrin as temporary matrix in a composite, which was divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…36 Tantalum scaffold with fibrin as cell carrier promotes chondrocyte proliferation and cartilaginous tissue formation. 37 In addition, porous tantalum begins to be applied as dental implants in animal experiments and in clinic. 38,39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Tantalum scaffold with fibrin as cell carrier promotes chondrocyte proliferation and cartilaginous tissue formation. 37 In addition, porous tantalum begins to be applied as dental implants in animal experiments and in clinic. 38,39…”
Section: Discussionmentioning
confidence: 99%
“…36 Tantalum scaffold with fibrin as cell carrier promotes chondrocyte proliferation and cartilaginous tissue formation. 37 In addition, porous tantalum begins to be applied as dental implants in animal experiments and in clinic. 38,39 ....................................................................................................................... Nevertheless, melting point of tantalum is about 3000 C, so porous tantalum with highly interconnected pores and uniform honeycomb structure is very difficult to obtain through the traditional technology.…”
Section: Discussionmentioning
confidence: 99%
“…All of these biomaterials have advantages as well as some drawbacks. Therefore, a combination of two or more of them is often used to develop new biomaterials known as composites [2] , [3] . Combination of natural protein-based polymers such as fibrin (excellent biocompatibility and bioactivity) with synthetic ones (versatility and mechanical strength) is a popular choice used in tissue engineering for a wide variety of tissues [4] , [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…12 Currently, porous Ta has been widely applied in orthopedic applications and oral implants, and studies have shown that it can highly promote the adhesion, proliferation, differentiation, and mineralization of osteoblasts in vitro 3,13,14 and in vivo. 15,16 In addition, recent studies have revealed that porous Ta combined with bone marrow stromal stem cells (BMSCs), 17 bone marrow mesenchymal stem cells (BMMSCs), 18 and fibrin 19 can better promote cell proliferation, bone integration, and regeneration. 20 Currently, a commercial PTTM-enhanced Ti dental implant is applied.…”
Section: Introductionmentioning
confidence: 99%